The Influence of Physical Quality, Staff Behavior, Perceived Price and Fairness, and Lifestyle Congruence on Brand Loyalty through Customer Satisfaction Among Guests at Whiz Prime Hotel Megamas Manado in Manado City - Hananiel Mennoverdi Gunawan; Rachel Anly Marilyn L Wullur (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
This study aims to examine the influence of Physical Quality, Staff Behavior, Perceived Price and Fairness, and Lifestyle Congruence on Brand Loyalty through Customer Satisfaction among guests at Whiz Prime Hotel Megamas Manado in Manado City. This research uses a quantitative method, with data processed using SPSS. A questionnaire was distributed to 60 respondents residing in Manado who had visited within the last five years. Staff Behavior and Customer Satisfaction were found to be the strongest predictors of Brand Loyalty. Lifestyle Congruence and Physical Quality also had significant effects on Brand Loyalty, although to a lesser extent, while Perceived Price and Fairness had no significant effect. For Customer Satisfaction, the greatest influence was from Staff Behavior, followed by Perceived Price and Fairness and Lifestyle Congruence; Physical Quality was not significant. Customer Satisfaction strongly drives Brand Loyalty, indicating that enhancing customer satisfaction can significantly boost loyalty. To increase Brand Loyalty, companies should focus on improving Staff Behavior, Perceived Price and Fairness, and Lifestyle Congruence.